Lanthanide Metal–Organic Frameworks Showing Luminescence in the Visible and Near‐Infrared Regions with Potential for Acetone Sensing. Issue 50 (6th November 2013) - Dang, Song; Min, Xue; Yang, Weiting; Yi, Fei‐Yan; You, Hongpeng; Sun, Zhong‐Ming
Abstract The luminescent properties of a family of lanthanide metal–organic frameworks LnL (Ln=Y, La–Yb, except Pm; L=4, 4′‐(2‐[(4‐carboxyphenoxy)methyl]‐2‐methylpropane‐1, 3‐diylbisoxy)dibenzoic acid) have been explored, and the energy‐transfer process in the compounds has been carefully analyzed. The visible‐emitting Tb0.08Gd0.92L and the near‐infrared (NIR)‐luminescent Yb0.10Gd0.90L show excellent optical performances and can be considered as fluorescent probes for acetone sensing based on luminescence quenching effects arising from host–guest interactions. Moreover, GdL exhibits a strong second harmonic generation (SHG) signal 6.1 times that of potassium dihydrogen phosphate (KDP) and an outstanding phase‐matchable effect. These lanthanide compounds combining fluorescent and nonlinear optical (NLO) properties could meet further requirements as multifunctional materials.